2014
DOI: 10.1371/journal.pone.0083184
|View full text |Cite|
|
Sign up to set email alerts
|

Arsenic Sulfide Promotes Apoptosis in Retinoid Acid Resistant Human Acute Promyelocytic Leukemic NB4-R1 Cells through Downregulation of SET Protein

Abstract: Tetra-arsenic tetra-sulfide (As4S4) is an arsenic compound with anti-tumor activity, especially in acute promyelocytic leukemia (APL) that are resistant to retinoic acid (RA). Although recent studies revealed that the therapeutic action of As4S4 is closely associated with the induction of cellular apoptosis, the exact molecular mechanism of action of As4S4 in RA-resistant APL remains to be clarified. In this study, we found that As4S4-induced apoptosis was accompanied by reduced mRNA and protein expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As 4 S 4 , an arsenic compound, has shown antitumor activities in malignancies, especially in APL, with limited toxicities. 14 18 The molecular mechanism of its antitumor activity is related to its ability to induce apoptosis 19 , 21 , 34 , 35 and the redistribution of PML-RARα protein in the leukemic cells. 20 …”
Section: Discussionmentioning
confidence: 99%
“…As 4 S 4 , an arsenic compound, has shown antitumor activities in malignancies, especially in APL, with limited toxicities. 14 18 The molecular mechanism of its antitumor activity is related to its ability to induce apoptosis 19 , 21 , 34 , 35 and the redistribution of PML-RARα protein in the leukemic cells. 20 …”
Section: Discussionmentioning
confidence: 99%
“…e efficacy of RIF in APL is not inferior to that of ATO due to its unique mechanism. As4S4, which is the main active ingredient of realgar in RIF, can induce apoptosis in HL-60 and NB4-R1 cells [36][37][38][39]. Wang and Liu et al demonstrated that As4S4 could significantly induce the degradation of the PML-RARα oncoprotein in mouse models and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is no doubt that PML-RARα plays a central role in the initiation of leukemogenesis, although there is evidence to suggest that the fusion gene expression is not the sole genetic event required for the development of APL [4][5][6]. It has been clarified that arsenic-mediated modulation/degradation of the PML-RARα oncoprotein is one of the major mechanisms responsible for the efficacy of arsenic compounds in APL [4][5][6]93]. Furthermore, the PML moiety, but not the RARα moiety, of the PML-RARα chimera represents the target for arsenic treatment [6,61].…”
Section: Degradation Of Pml-rarαmentioning
confidence: 99%
“…It has been clarified that both PML and PML-RARα form high-molecularweight conjugates with a small ubiquitin-related modifier (SUMO)-1 and are recruited from the nucleoplasm to the nuclear body (NB), followed by ubiquitin-mediated proteolysis [94][95][96]. Degradation of PML-RARα is closely associated with differentiation, growth inhibition associated with the induction of apoptosis, as well as cell cycle arrest in APL cells treated with arsenic compounds [4][5][6]93]. In addition, degradation of the PML-RARα protein associated with its redistribution was also reported in fresh APL cells obtained from the PB and BM of APL patients after treatment with As 4 S 4 [97].…”
Section: Degradation Of Pml-rarαmentioning
confidence: 99%
See 1 more Smart Citation